SIKLUS BELAJAR 7-E DENGAN PENDEKATAN SAINTIFIK PADA KURIKULUM 2013 DALAM PEMEBLAJARAN FISIKA SISWA KELAS X MIA SMA - Doni Martha; Yurnetti Yurnetti; Hidayati Hidayati (PILLAR OF PHYSICS EDUCATION, 2015)
Learning activities should be able to involved students actively in accordance with the demands in Curriculum 2013, in which the students were demanded to have some learning experiences such as observing, asking, trying or collecting information, logical reasoning or associating and communicating. One of the alternatives to improve student’s involvement is the Cycling Learning Strategy concerning to the result of Physic subject learning in grade X MIA SMAN 1 Ranah Pesisir. The purpose of this research is to know the Influence of Applying 7-E Model Learning Cycle with Scientific Approach to Curriculum 2013 toward the Result of Physic Subject Learning in grade X MIA SMAN 1 Ranah Pesisir. Research type for this experiment is Quasi Experimental Research with Randomized Control Group Only Design. Population of research is all of grade X MIA students in SMAN 1 Ranah Pesisir who registered in the year of 2014/2015. Sample taking was done by using Cluster Sampling technique. Research sample prioritized grade X MIA4 as experimental class and grade X MIA3 as control class with identical number of sampling objects. Research data included competencies of three categories namely attitude, knowledge and skills. Research instrument in the form of learning result test was done for knowledge, observation sheets were done for attitude and performance rating sheets were done for skills. Data analysis technique was using test of similarity with two averages in the real value result 0,05 According to the data of experimental result, the results of student’s learning in the category of knowledge, attitude and skills can be retrieved from each of experimental classes which shows 80,02, 84,08, 78,59 and 81,72. They were higher than the control classes that shows 71,57, 78,09, 73,44 and 76,31. So it can be concluded that the application of 7-E Model Learning Cycle with scientific approach to Curriculum 2013 have a significant influence for the result of Physic subject learning in grade X MIA SMAN 1 Ranah Pesisir in category of attitude, knowledge and skills with the real value result 0,05